Dimensions of the collective on motorcycle messengers’ work activity - Moraes, Thiago Drumond (2014)
Brazilian Public Policies seek to reduce the severity of motorcycle messengers work accidents, prioritizing individual dimensions of piloting. Their results are limited by not satisfactorily consider collective dimensions of work and its effects on profession. Moreover, there is lack of research in this field. Cooperating to movement of understand↔transform, was aimed to verify how professional collective has been developing within motorcycle messengers’ professional milieu. Guided by Ergology, in the research were mobilized clinical approaches of work: Psychodynamic of Work and Clinic of Activity. Was observed the existence of professional collective in formation, verified by practical knowledge, defensive systems, professional languages, values and rules of craft, which began to be produced and shared among workers. However, was found that individualism and low solidarity among peers undermine the work’s collective in formation, reducing its ability to respond to degrading working conditions. It is understood inevitable its strengthening to pursue safer professional practice.